Reinterpretation of the Values of Religious Moderation and Its Internalization among Gen Z Indonesian Muslims - Farida, Umma; Amaliyah, Efa Ida; Rahman, Azka Fayyad Atqia (FIKRAH, 2026)
This article aims to reinterpret the values of religious moderation in the Qur’an and Hadith and the implementation of its internalization towards Gen Z Muslims in Indonesia. This research is qualitative research that combines literature review and field study. The literature review is to uncover the values of religious moderation according to Islamic teachings, namely the Qur’an and Hadith, while the field study is to see the implementation of the internalization of these values of religious moderation towards Gen Z Muslims in Indonesia. The data collection techniques in this study used documentation, interview, and observation methods, then analyzed descriptively-critically. The values of religious moderation according to the Qur’an and Hadith include: (1) humanity, (2) public welfare, (3) justice, (4) balance, (5) obedience to the constitution, (6) national commitment, (7) tolerance, (8) anti-violence, (9) respect for tradition. The Qur’an and Hadith also emphasize prioritizing global and universal interests to avoid danger and harm to the public. The implementation of religious moderation values for Indonesian Muslim Gen Z is urgent. It aims to shape their tolerant and multicultural attitudes and erode radicalism and intolerance based on religion and belief. In addition, the application of these religious moderation values also aims to foster values of peace so that various acts of radicalism and violence in the name of religion in Indonesia in the future can be reduced and minimized.